Knowledge mapping of immune thrombocytopenia: a bibliometric study - Wu, Feifeng; Li, Cuifang; Mao, Jueyi; Zhu, Junquan; Wang, Yang; Wen, Chuan (Frontiers in Immunology, 2023)
Background Immune thrombocytopenia (ITP) is an autoimmune disease characterized by isolated thrombocytopenia. Recently, the pathophysiology and novel drugs of ITP have been the focus of researchers with plenty of publications emerging. Bibliometrics is the process of extracting measurable data through statistical analysis of published research studies to provide an insight into the trends and hotspots. Objective This study aimed to provide an insight into developing trends and hotspots in the field of ITP by bibliometric analysis. Methods By using three bibliometric mapping tools (bibliometrix R package, VOSviewer, CiteSpace), we summarized the overview information of retrieved publications, as well as the analysis of keyword co-occurrence and reference co-citation. Results A total of 3299 publications with 78066 citations on ITP research were included in the analysis. The keyword co-occurrence network identified 4 clusters relating to the diagnosis, pathophysiology, and treatment of ITP respectively. Then the reference co-citation analysis produced 12 clusters with a well-structured and highly credible clustering model, and they can be divided into 5 trends: second-line treatment, chronic ITP, novel therapy and pathogenesis, COVID-19 vaccine. Treg cells, spleen tyrosine kinase, and mesenchymal stem cells were the latest hotspots with strong burstness. Conclusion This bibliometric analysis provided a comprehensive insight into research hotspots and trends on ITP, which would enrich the review of the ITP research.